Improving Students' Cognitive Learning Achievement in History Learning Through the Cooperative Script Model and Infographic Media in Class X IPS 1 MA Negeri 2 Surakarta - Siti Nurjanah; Sriyanto Sriyanto (Proceedings Series on Social Sciences & Humanities, 2025)
The purpose of this study is to improve students' cognitive learning achievement in history learning through the cooperative script model and infographic media. This study uses a quantitative approach with an experimental method in one class. Data collection was carried out through pretest, posttest and observation. The data analysis technique used SPSS with the Paired Sample T Test technique. Based on the results of the study, the Sig. (2-tailed) value was obtained at 0.000 <0.05, so we can conclude that there is a significant difference between learning outcomes in the Pre-test and Post-test data.